Parcelized Cut-and-Carry Agroforestry Systems for Confined Livestock - Seruni, A.P.; Aguilar, F.X.; Cai, Z.; Gold, M.A.; Roshetko, J.M. (Springer, 2021)
We characterize a parcelized land management system that does not meet traditional co-located agroforestry practices in the tropics. A cut-and-carry agroforestry system for confined livestock emphasizes land utilization as a source of fodder, cutting and carrying feed from parcels to paddocks near a farmer’s home. It reduces feed cost by utilizing parcels under private, shared, and/or public ownership. Within cut-and-carry systems, we distinguish between those where parcels are managed as monocrops and traditional co-located agroforestry practices. Primary data for our case study were collected by surveying heads of household in Central Java, Indonesia, and analyzed following a capitals-based rural livelihoods framework. A sample of 122 farmers who managed parcels under co-located agroforestry practices was compared against 50 farmers who implemented parcelized monocropping. Overall, the adoption of cut-and-carry systems supports financial resiliency by limiting cash expenditures, facilitating income diversification, and producing assets that meet planned market opportunities and unforeseen cash needs. Survey results show that farmers who engage in parcelized agroforestry have more farming experience, higher farming income, are located at higher elevations, and live farther from the nearest local market. On-farm income among agroforestry cut-and-carry farmers was on average 11.1% higher than those using a cut-and-carry system but only adopting monocrop practices. Land as a biophysical capital asset under full private-ownership and at higher altitudes, and longer farming experience as a human capital asset, increased the likelihood of adopting parcelized co-located agroforestry practices. Membership in cash-crop cooperatives as a form of social capital asset was associated with a higher likelihood of managing land as parcelized monocrops.